Pretreatment with nitric oxide reduces lead toxicity in cowpea (Vigna unguiculata [L.] walp.) - Sadeghipour Omid (Archives of Biological Sciences, 2016)
Lead (Pb) is one of the most important toxic heavy metals that reduce plant growth and development. Therefore, finding compounds that can alleviate the toxic effects of Pb is necessary. Nitric oxide (NO) is a signaling molecule that plays important roles in different physiological processes in plants, such as the response to biotic and abiotic stresses. A pot experiment was conducted to study the effects of exogenously applied NO on Pb stress tolerance in cowpea. Seeds were soaked at various concentrations of sodium nitroprusside (SNP; NO donor) (0, 0.5 and 1 mM) for 20 h, and then sown in pots containing 0 or 200 mg kg-1 Pb (NO3)2. The obtained results showed that Pb stress significantly reduced the chlorophyll value, relative water content (RWC) and net photosynthetic rate, but increased lipid peroxidation, proline content and superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) activities. Nonetheless, different levels of NO significantly lowered Pb toxicity by further increasing SOD, CAT, APX and GR activities as well as proline accumulation. NO pretreatment also raised the chlorophyll value, RWC and net photosynthetic rate but reduced lipid peroxidation. Both NO levels (0.5 and 1 mM) were effective in Pb stress tolerance; however, 0.5 mM was more effective. These results indicate that NO pretreatment plays an important role in protecting cowpea plants against Pb toxicity by enhancing antioxidant enzyme activities and proline accumulation.